USE OF THE RETROSPECTIVE METHOD FOR THE DETERMINATION OF BIRTH AND DEATH RATES IN RURAL COMMUNITIS - A. Mossadeh; A. Arvanaghi; A. Nadim (Iranian Journal of Public Health, 1972)
There are several methods to determine the Birth Rate and the Death Rate (B.R. & D.R) in deve1oping countries. In this study, we have used a retrospective method in a group of villages that have been under surveillance for another purpose. The area under survey consists of 23 villages in Isfahan with a population of 9,839. The B.R. and D.R. found in this survey were 13 and 40.8 per thousand respectively. Due to the under enumeration, of deaths under one year of age the rate have been corrected. The final results were 17 per thousand for D.R. and 44.7 per thousand for B.R. the are relatively acceptable for the area.